Eco-Biological Studies on Wild Sunflower (Verbesina encelioides) in the Central Rift Valley of Ethiopia : Eco-Biology of Wild Sunflower - Amare Fufa; Taye Tessema; Zelalem Bekeko; Tewodros Mesfin (Pest Managment Journal of Ethiopia, 2021)
Wild sunflower threatens crop production, animal husbandry, and biodiversity in areas where it has spread. Even though the weed has already concurred huge areas of different land use systems of the Central Rift Valley, there is no available information on its eco-biology. Thus, this study was conducted to generate eco-biological information on wild sunflower by investigating the effects of different seasons of the year, soil ploughing, seed storage time, and burial depth on seed germination and seedling emergence. Wild sunflower matured in about 128 to 141 days, during which it attained a height of up to 82 cm. The weed could produce up to 22 branches and 32 flower heads per plant. The weed attained a biomass yield of about 26 and 34 g plant-1 at Adamitulu and 35 and 44 g plant-1 at Melkassa at flowering and maturity, respectively. Wild sunflower produced 813 to 1124 seeds per plant. Seedling emergence m-2 averaged 42.6 at Melkassa and 34.4 at Adamitulu under unploughed soil but declined to 23.8 and 20.6, respectively, when the plot was ploughed. During the summer, the highest seedling densities of 38.3 and 54.7 plant m-2 emerged at Adamitulu and Melkassa, respectively. The proportion of germinating seeds was highest in seeds stored for 24 weeks (97%), and emergence increased with increasing storage time until germination stabilized while only 2% germinated from freshly harvested seeds. The required storage time for 50% germination was only 2.8 weeks. The percentage of seedling emergence was highest for seeds placed on the soil surface (94%), and decreased with the burial depth; no seedlings emerged from a depth of 6 cm. It was observed that a burial depth of only 2.7 cm reduced seedling emergence by 50%. Overall, the information generated on the biology and ecology of wild sunflower in this study will assist in the development of its management strategies.